Combined Use of Common Fecal and Blood Markers for Detection of Endoscopically Active Inflammatory Bowel Disease. Issue 3 (2nd March 2020) - Mak, Lung-Yi; Tong, Teresa S. M.; Cheung, Ka-Shing; Chen, Li-Jia; Lui, Ka-Luen; Lau, Kam-Shing; Leung, Wai K.
Abstract : INTRODUCTION: Monitoring of disease activity is essential in patients with inflammatory bowel disease. Although endoscopic remission is the ideal therapeutic goal, noninvasive biomarkers (blood and fecal) are more acceptable to patients and are less costly. We evaluated the performance of combinations of fecal and blood markers on the detection of endoscopically active disease. METHODS: Patients with ulcerative colitis (UC) or Crohn's disease (CD) on stable medications were recruited. Blood markers included C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), albumin, platelet count (PLT), and hemoglobin. Fecal biomarkers included fecal calprotectin (FCT) and fecal immunochemical test (FIT). These markers were compared with the endoscopic Mayo score for UC and the Simple Endoscopic Score for CD. RESULTS: One hundred thirteen patients (mean age 44.7 years, 63.7% men, 54.9% patients with UC and 45.1% patients with CD) were recruited. FCT correlated well with FIT ( r = 0.58), CRP ( r = 0.56), ESR ( r = 0.40), albumin ( r = −0.54), PLT ( r = 0.61), and hemoglobin ( r = −0.35; all P s < 0.001). Among 66 patients with endoscopic evaluation, 39.4% with endoscopically active disease had higher FCT, FIT, CRP, ESR, PLT, lower albumin, and hemoglobin compared with those in endoscopic remission (all P s < 0.01). All 7 markers demonstrated good area under receiver operating characteristics (>0.7), with FCT being the best (0.91) for endoscopically active disease. Combining FCT and FIT improved the specificity to 95%, but the sensitivity decreased to 65.4%. In the subgroup analysis of UC, adding PLT to FIT improved the sensitivity and specificity to 100% and 90.9%, respectively. DISCUSSION: The combined use of fecal biomarkers and blood indexes is superior to the use of fecal biomarkers alone in identifying endoscopically active disease.